2016
DOI: 10.1017/s1751731115002438
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of haematological profiles and whole blood relative gene expression levels in Holstein-Friesian and Jersey bull calves undergoing gradual weaning

Abstract: Haematological profiles indicate the health status of an animal and can be used to identify sub-clinical stress responses. The objectives of the study were to examine (i) the effect of breed and plane of nutrition, on haematological profiles of artificially reared Holstein-Friesian and Jersey bull calves in response to gradual weaning, and (ii) the effect of breed on immune response genes in bovine whole blood using real-time quantitative PCR. Holstein-Friesian and Jersey bull calves were group housed indoors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…This is probably because all calves received adequate nutrition (i.e., more than maintenance). This study and our previous study (Johnston et al, 2016a) have demonstrated that feeding greater amounts of MR and Interactions: HS ´ N is an interaction between "health score (HS)" and "plane of nutrition (N)"; HS ´ B is an interaction between "health score (HS)" and "breed (B)"; N ´ B is an interaction between "plane of nutrition (N)" and "breed (B)".…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This is probably because all calves received adequate nutrition (i.e., more than maintenance). This study and our previous study (Johnston et al, 2016a) have demonstrated that feeding greater amounts of MR and Interactions: HS ´ N is an interaction between "health score (HS)" and "plane of nutrition (N)"; HS ´ B is an interaction between "health score (HS)" and "breed (B)"; N ´ B is an interaction between "plane of nutrition (N)" and "breed (B)".…”
Section: Discussionsupporting
confidence: 59%
“…This experiment was conducted as part of a larger study, and therefore, the animal model and management have previously been described by Johnston et al (2016a). For clarity, it is also briefly outlined here.…”
Section: Animal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The health status of these animals from initiation of dietary treatments until 14 days post-weaning has been characterized in detail [24].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Another approach for automatic lameness detection, gait behaviour and ground reaction forces, is proposed by van Nuffel et al (2016). IR-thermography-based monitoring of body temperature of calves (Hoffmann et al, 2016) and gene expression of calves undergoing gradual weaning (Johnston et al, 2016) are presented in this special issue.…”
mentioning
confidence: 99%